Ribose-5-phosphate metabolism protects E. coli from antibiotic lethality - Tatyana Seregina; Rustem Shakulov; Giulio Quarta; Konstantin Shatalin; Svetlana Sklyarova; Irina Petrushanko; Artemy P. Fedulov; Alexander V. Ivanov; Vladimir Mitkevich; Alexander Makarov; Alexander S. Mironov; Evgeny Nudler (mBio)
ABSTRACT In Escherichia coli, ribose-5-phosphate (R5P) biosynthesis occurs via two distinct pathways: an oxidative branch of the pentose phosphate pathway (PPP) originating from glucose-6-phosphate, and a reversed non-oxidative branch originating from fructose-6-phosphate, which relies on transaldolases TalA and TalB. Remarkably, we found that disrupting the oxidative PPP branch by deleting the zwf gene significantly increased bacterial susceptibility to killing by a variety of antibiotics. Surprisingly, additional mutations in the talA and talB genes further enhanced bacterial sensitivity to oxidative stress and antibiotic-mediated killing though they had little impact on the minimal inhibitory concentrations (MICs). The hypersensitivity observed in the zwf talAB mutant could be fully reversed by the processes that either utilize R5P or limited its accumulation. Specifically, activating the purine biosynthetic regulon or inhibiting nucleoside catabolism via deoB gene inactivation, which blocks the conversion of ribose-1-phosphate to R5P, restored bacterial tolerance. Furthermore, enhancing the biosynthesis of cell wall component ADP-heptose from sedoheptulose-7-phosphate suppressed antibiotic killing of the zwf talAB mutant. Biochemical analysis confirmed a direct link between elevated intracellular R5P levels and increased bacterial susceptibility to antibiotics-induced killing. These findings suggest that targeting the PPP could be a promising strategy for developing new therapeutic approaches aimed at potentiating clinically relevant antibiotics.IMPORTANCERecent studies have revealed the crucial role of bacterial cell’s metabolic status in its susceptibility to the lethal action of antibacterial drugs. However, there is still no clear understanding of which key metabolic nodes are optimal targets to improve the effectiveness of bacterial infection treatment. Our study establishes that the disruption of the canonical pentose phosphate pathway induces one-way anabolic synthesis of pentose phosphates (aPPP) in E. coli cells, increasing the killing efficiency of various antibiotics. It is also demonstrated that the activation of ribose-5-phosphate utilization processes restores bacterial tolerance to antibiotics. We consider the synthesis of ribose-5-phosphate to be one of the determining factors of bacterial cell stress resistance. Understanding bacterial metabolic pathways, particularly the aPPP’s role in antibiotic sensitivity, offers insights for developing novel adjuvant therapeutic strategies to enhance antibiotic potency.